The aberrant Esie head as model: an insight into the styles and origin of the Esie stone carvings (2000)
lfe is incontrovertibly the most important Yoruba town in terms of art, religion and culture, it is therefore advantaged as a possible source place to solve the problem of the enigma surrounding the Esie stone carvings. This hypothesis is pursed to the conclusion that lfe is the most likely place that could have conditioned the Esie stone carving in their present location. An aberrant stone head, the largest among the over 800 stone carvings found in Esie is stylistically and culturally compared and linked with other Yoruba stone carvings from lfe and indeed a group of naturalistically carved stones also identified among the Esie corpus. This leads to conclusion of an lfe impetus for the creation of the Esie stone carvings